2012
DOI: 10.1021/la303032f
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Oriented Immobilization on Gold using the Reaction between Carbon Disulfide and Amine Groups and Its Application in Immunosensing

Abstract: Carbon disulfide (CS 2 ) can spontaneously react with amine groups to form dithiocarbamates on gold surface, providing the possibility to immobilize some compounds with primary or secondary amine groups in one step. Using this principle, an immunosensor interface prepared for immunoglobulin G (IgG) sensing surface toward anti-IgG has been fabricated for the first time by simply immersing gold slides into a mixed aqueous solution of CS 2 and protein A, followed by incubation in immunoglobulin G solution. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Prior to use the slides were rinsed with water and ethanol and cleaned in a UV chamber for 45 min. For ellipsometry and AFM analysis, gold substrates manufactured by Arrandee consisting of a thin film (200 nm) of gold on borosilicate glass (1.1 × 1.1 cm 2 ) with a chromium undercoat (2-4 nm) were used and cleaned in piranha solution (H 2 SO 4 /H 2 O 2 = 3:1, v/v) and in a UV chamber for 45 min as described elsewhere [5,27]. These latter substrates were also flameannealed after which they acquired a preferential (111) orientation, as proved by scanning tunneling microscopy measurements [28].…”
Section: Preparation Of Gold Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to use the slides were rinsed with water and ethanol and cleaned in a UV chamber for 45 min. For ellipsometry and AFM analysis, gold substrates manufactured by Arrandee consisting of a thin film (200 nm) of gold on borosilicate glass (1.1 × 1.1 cm 2 ) with a chromium undercoat (2-4 nm) were used and cleaned in piranha solution (H 2 SO 4 /H 2 O 2 = 3:1, v/v) and in a UV chamber for 45 min as described elsewhere [5,27]. These latter substrates were also flameannealed after which they acquired a preferential (111) orientation, as proved by scanning tunneling microscopy measurements [28].…”
Section: Preparation Of Gold Surfacesmentioning
confidence: 99%
“…The thickness of the lipid film was estimated as reported in the literature [5,27] fixing the real part of the refractive index at 1.5 [29,30]. The very low extinction coefficient values (k) obtained in this work ranged from 0.03 to 0.11, which indicates nearly transparent films, as expected for thin organic layers [27]. A thorough rinse with buffer and water (and ethanol in the case of MUA SAM deposition) and ellipsometric measurements were done between each modification step.…”
Section: Ellipsometrymentioning
confidence: 99%
“…However, this method requires the incorporation of an activation step, usually performed with N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), to attach the protein to the SAM [8][9][10]. An approach using the in situ formation of dithiocarbamates (DTC) to, in only one-step, immobilize compounds with amine groups to gold surfaces has been developed as an efficient alternative [11][12][13]. Briefly, carbon disulfide spontaneously reacts with amine groups to form DTC through the immersion of gold substrates in a solution containing CS 2 and the compound to immobilize, at room temperature [11,14,15], without the need of adding several modification and activation steps.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has been used to immobilize a wide range of molecules and biocompounds [13,[17][18][19][20][21] and, importantly, to prepare immunosensor interfaces for the detection of biological molecules relying on the specific antibody-antigen reaction. Furthermore, the ability to prevent protein nonspecific adsorption to the biorecognition surfaces has been also demonstrated [12].…”
Section: Introductionmentioning
confidence: 99%
“…This ability to specifically bind antibodies aligned in a precise orientation has been utilized to develop antibody-based detection systems [8]- [10]. Studies have also shown that immunoglobulin molecules can be successfully tethered to metals such as gold [10]- [13] and stainless steel [14] by using recombinant PG.…”
Section: Introductionmentioning
confidence: 99%